Systematic review and meta‐analysis: assessment of factors affecting disability in inflammatory bowel disease and the reliability of the inflammatory bowel disease disability index. Issue 1 (9th October 2017) - Lo, B.; Prosberg, M. V.; Gluud, L. L.; Chan, W.; Leong, R. W.; van der List, E.; van der Have, M.; Sarter, H.; Gower‐Rousseau, C.; Peyrin‐Biroulet, L.; Vind, I.; Burisch, J.
Summary: Background: The Inflammatory Bowel Disease Disability Index (IBD‐DI) has recently been developed for patients with Crohn's disease (CD) and ulcerative colitis (UC). Aim: To assess the severity of disability and associated factors using the IBD‐DI, and review the validity of the IBD‐DI as a tool. Method: Systematic review of cross‐sectional studies. Patients included had UC or CD and were classified as active, in remission, or needing surgery, biological and/or steroid treatment. We included studies assessing disability using the IBD‐DI and that were captured by electronic and manual searches (January 2017). The possibility of bias was evaluated with the Newcastle‐Ottawa Scale. Results: Nine studies were included with 3167 patients. Comparatively, patients with active disease had higher disability rates than those in remission (SMD [CI95] = 1.49[1.11, 1.88], I 2  =  94%, P <.01), while patients on biological treatment had lower disability rates than those receiving corticosteroid treatment (SMD [CI95] = −0.22[−0.36, −0.08], I 2  = 0%, P <.01). Disease activity and unemployment were found to be associated factors. The IBD‐DI scored "good" for internal consistency, "fair" to "excellent" for intra‐rater reliability and "excellent" for inter‐rater reliability. Construct validity was "moderately strong" to "very strong" and structural validity was found to be mainly unidimensional. The IBD‐DI had excellent responsiveness, while its interpretability was only useful on a group level. Conclusions: This systematic review and meta‐analysis found a significant association between disease activity, treatment received and disability; although significant heterogeneity was found. The IBD‐DI is reliable and valid, but further studies are needed to measure its interpretability. Abstract : Linked Content This article is linked to Sawbridge and Subramanian paper. To view this article visithttps://doi.org/10.1111/apt.14413 .